2014
DOI: 10.1021/am500138q
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth-Modified Kaolin/NaY-Supported Pd–Pt Bimetallic Catalyst for the Catalytic Combustion of Benzene

Abstract: A new type of porous kaolin/NaY composite (KL-NY) with a large specific surface area and large pore sizes was synthesized through a one-step crystallization process, and rare earth-modified KL-NY-supported Pd-Pt catalysts were studied for benzene combustion. The results indicated that the pore volume and specific surface area of KL-NY after calcination and crystallization were 0.298 cm(3)/g and 365 m(2)/g, respectively, exhibiting appropriate pore structure and good thermal stability. Catalysts with rare earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…1,[33][34][35][36][37][38]43 To some extent, an agreement between the simulation and experimental data was achieved. 1,[33][34][35][36][37][38]43 To some extent, an agreement between the simulation and experimental data was achieved.…”
Section: Introductionmentioning
confidence: 55%
“…1,[33][34][35][36][37][38]43 To some extent, an agreement between the simulation and experimental data was achieved. 1,[33][34][35][36][37][38]43 To some extent, an agreement between the simulation and experimental data was achieved.…”
Section: Introductionmentioning
confidence: 55%
“…Hutchings et al investigated the oxidation of toluene over the Au-Pd catalysts and demonstrated that the Au acted as an electronic promoter for Pd (Enache et al, 2006;bin Saiman et al, 2012). The complete conversion of benzene could be achieved at approximately 230°C owing to the enhancement of the oxidation properties over Pd catalysts with the addition of Ce and Pt (Zuo et al, 2014). Researchers have attempted to improve low-temperature activity and stability of Pd-supported catalysts through introducing non-noble metals to the catalysts, concerning the high cost and the rare supply of the noble metals.…”
Section: Alloyed Nanoparticle Catalystsmentioning
confidence: 99%
“…Generally, kaolin is used as additives in ceramics, rubber, paper as well as used as catalytic applications . Given the abundancy and cost‐efficiency, it has recently attracted great attention in and water treatment catalyst support …”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Given the abundancy and cost-efficiency, it has recently attracted great attention in and water treatment catalyst support. [4][5][6] Kaolinite, often found as coal-bearing kaolin, is a companion clay in many coal mines found in Inner Mongolia region of China. According the Mining Bureau of the United States of the interior, the estimated global reserves of kaolin is proven to be around 12.2 billion tons.…”
Section: Introductionmentioning
confidence: 99%